Effects of manganese doping on the dielectric properties of titanium dioxide ceramics - Iis, Sopyan; Singh, Ramesh; Nawawi, Natasha Ahmad; Anna, Tampieri; Simone, Sprio (Pergamon, 2011)

(untitled)
We have investigated the effect of manganese (Mn) doping on properties of nanosized biphasic calcium phosphate powders and their dense bodies. Manganese levels of 0.6, 1.3, 1.9, 4.3, 7.0 and 11.9 at.% were successfully incorporated into biphasic calcium phosphate via a sol–gel route. The prepared powders were calcined at temperatures of 500–1200 °C. The X-ray diffraction analysis revealed that a mix phase comprising of hydroxyapatite and β-tricalcium phosphate were present, however the content of each phases in the structure was affected by the Mn content. The studies found that the largest portion of β-tricalcium phosphate was detected at 4.3 at.% Mn doping. The incorporation of Mn has also greatly increased the crystallinity of the biphasic calcium phosphate powder due to progressive densification of particles. Characterization on their sintered dense bodies showed that manganese concentration affected the physical properties of the dense bodies. The highest density was found for 4.3 at.% Mn doped biphasic calcium phosphate sintered at 1300 °C.